Emotional Mental Disorders on Clients Pandemic Covid 19 at Quarantine House - Siti Nurjanah (Jurnal Ilmu Keperawatan Jiwa, 2020)
Emotional mental disorders can occur due to pandemic Covid 19. This condition has a physical and psychological impact on each individual, especially the people who have to undergo isolation/quarantine because of Covid 19. The community should stay in a special quarantine house because it is considered unable to do self-quarantine at home and potentially to spread Covid 19. The purpose of this research is to get an overview of emotional mental disorders on clients residing in quarantine houses. This type of research is quantitative research. This research is quantitative research. This method of research is descriptive analytic on 30 clients who live in quarantine house consisting of clients who have been through Rapid Test and Swab related to Covid 19. The sampling process was carried out in total sampling, a picture of the emotional mental disorder on the client using SRQ 29 (Self Report Quesionarre 29). The results of the study gained 10 people (33.3%) Experiencing emotional mental disorders. The most complaints are somatis complaints like feeling anxious (40%) And abandoned day-to-day activities (37%). There is a need to have a psychiatric problem approach to Covid 19 clients who live in quarantine houses.